Enzyme biotechnology development for treating polymers in hydraulic fracturing operations. Issue 3 (11th January 2021) - Scheffer, Gabrielle; Berdugo‐Clavijo, Carolina; Sen, Arindom; Gieg, Lisa M.
Summary: Carboxymethyl cellulose (CMC) is a polymer used in many different industrial sectors. In the oil and gas industry, CMC is often used during hydraulic fracturing (fracking) operations as a thickening agent for effective proppant delivery. Accumulations of CMC at fracture faces (known as filter cakes) can impede oil and gas recovery. Although chemical oxidizers are added to disrupt these accumulations, there is industrial interest in developing alternative, enzyme‐based treatments. Little is known about CMC biodegradation under fracking conditions. Here, we enriched a methanogenic CMC‐degrading culture and demonstrated its ability to enzymatically utilize CMC under the conditions that typify oil fields. Using the extracellular enzyme fraction from the culture, significant CMC viscosity reduction was observed between 50 and 80˚C, at salinities up to 20% (w/v) and at pH 5–8 compared to controls. Similar levels of viscosity reduction by extracellular enzymes were observed under oxic and anoxic conditions. This proof‐of‐concept study demonstrates that enzyme biotechnology holds great promise as a viable approach to treating CMC filter cakes under oilfield conditions. Abstract : Extracellular enzymes able to hydrolyze carboxymethyl cellulose (CMC) are shown to reduce the viscosity of this polymer used in the oil and gas industry. The enzymes are effective at high temperatures and salinities, thus this proof‐of‐concept study demonstrates that enzyme biotechnology can be a viable approach to treat CMC filter cakes in oilfield operations.